ETNO TRADITIONAL ACCOUNTING: ACCOUNTS RECEIVABLE AND ACCOUNTS PAYABLE ACCOUNTING AND THEIR RELEVANCE TO THE TIME VALUE OF MONEY - Fatimatus Syafira; Ira Hasti Priyadi; Riskiyatul Khasanah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to explore accounting values in the local tradition of otok-otok and examine their relevance to the concept of time value of money from an ethno-accounting perspective. Otok-otok is a routine tradition of the Madurese people, similar to an arisan, which is carried out in turns with the aim of strengthening family ties and maintaining family harmony. This tradition is not only social in nature but also has accounting value as a form of collective savings (ompangan), for example, for weddings. This tradition focuses more on family routines or the family's intention to carry out otok-otok traditions such as circumcision, building a house, and requires capital based on trust and a sense of responsibility. Uniquely, otok-otok does not involve profit or interest in a continuous period, but rather a sense of shame, responsibility and kinship. This study uses a qualitative approach with ethnographic methods through observation, interviews and documentation in Bulang Hamlet, Pangilen Village, Sampang Subdistrict, Sampang Regency. The results of the study show that the otok-otok tradition, which is simply recorded in the jhelen book, still reflects the principle of time value of money without a formal discount mechanism. Thus, the otok-otok tradition is a cultural heritage as well as an alternative community financial system that is inclusive, fair, and sustainable